2010
DOI: 10.1037/a0017688
|View full text |Cite
|
Sign up to set email alerts
|

Verbal-spatial and visuospatial coding of number–space interactions.

Abstract: A tight correspondence has been postulated between the representations of number and space. The spatial numerical association of response codes (SNARC) effect, which reflects the observation that people respond faster with the left-hand side to small numbers and with the right-hand side to large numbers, is regarded as strong evidence for this correspondence. The dominant explanation of the SNARC effect is that it results from visuospatial coding of magnitude (e.g., the mental number line hypothesis). In a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
223
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(244 citation statements)
references
References 61 publications
(80 reference statements)
16
223
4
1
Order By: Relevance
“…Verbal processing was observed as the dominant mechanism in adults (Gevers et al, 2010). In line with the conclusions of Van Galen and Reitsma (2008), it could be expected that verbal processing is also the dominant mechanism in children, at least when magnitude information is relevant to the task.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…Verbal processing was observed as the dominant mechanism in adults (Gevers et al, 2010). In line with the conclusions of Van Galen and Reitsma (2008), it could be expected that verbal processing is also the dominant mechanism in children, at least when magnitude information is relevant to the task.…”
supporting
confidence: 67%
“…A previous study showed that verbal coding dominates the SNARC effect in adults (Gevers et al 2010). The present study shows that the SNARC effect in 9 and 11 year old children is also more dominantly driven by verbal coding.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This work provides empirical data in support of recent computational models of number representation Gevers, Verguts, Reynvoet, Caessens, & Fias, 2006) and showing that a purely embodied perspective is likely insufficient to account for the observed associations between symbolic number and space (Santens & Gevers, 2008;Gevers et al, 2010). Further, the present study adds to a growing body of work on the dynamics of cognitive processing, representing diverse topics such as stereotype formation (Freeman & Ambady, 2009), voice processing (Sulpizio et al, 2015), language comprehension (Spivey et al, 2005;Incera & McLellan, 2015), memory (Abney, McBride, Conte, & Vinson, 2014;Papesh & Goldinger, 2012), and face processing (Freeman & Ambady, 2011;Hehman, Carpinella, Johnson, Leitner, & Freeman, 2014).…”
Section: Discussionsupporting
confidence: 77%